2021
DOI: 10.4103/jpbs.jpbs_704_20
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Rheumatoid Arthritis: A Case Control Study

Abstract: Introduction: Association between oral health and rheumatoid arthritis is well established. Oral health-related quality of life was determined in patients diagnosed with rheumatoid arthritis (RA). Materials and Methods: This study was conducted among 45 patients (males 25 and female 20) (Group I) of RA and 45 healthy participants as control (Group II). Disease activity score 28 test, health assessment questionnaire (HAQ), and general oral health assessment index (GOHAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…This might explain the lack of association between RA and oral health in the elderly. Previous studies showed interactions in sex [44,45], smoking [27], and frequency of toothbrushing [18] stratification, but in this study, there was no considerable difference even after adjustment in the stratified subgroup analysis.…”
Section: Discussioncontrasting
confidence: 89%
“…This might explain the lack of association between RA and oral health in the elderly. Previous studies showed interactions in sex [44,45], smoking [27], and frequency of toothbrushing [18] stratification, but in this study, there was no considerable difference even after adjustment in the stratified subgroup analysis.…”
Section: Discussioncontrasting
confidence: 89%
“…According to Nosratzehi et al (2019), the total GOHAI score was 37.46±9.3 and 53.21±11.3 in rheumatoid arthritis and control groups, respectively [ 24 ]. Moreover, according to Ahmed et al(2021), the total GOHAI score was 34.6 and 52.8 in RA and control groups, respectively [ 26 ]. In both studies, the difference was significant, which showed lower oral health-related quality of life in rheumatoid arthritis cases.…”
Section: Discussionmentioning
confidence: 99%